It takes two to make an accident : HISK Laureates : 2015. - Simpson, Helen; Ertan, Yavuz (Gent : HISK / Hoger Instituut voor Schone Kunsten, 2015)
Kristbjörg Sigurðardóttir; Jóhanna ; Crispino, Raffaella ; Aydoslu, Leyla ; Bisig, Flurin ; Lefebvre, Marie-Fleur ; Vanhee, Klaas ; de Senna, Tramaine ; Van Herreweghe, Egon ; Littwitz, Ella ; Cottin Stefanelli, Laure ; Alavanou, Loukia ; Verhoeven, Benjamin ; Van der Auwera, Emmanuel
It takes two to make an accident, HISK Laureates 2015, HISK, Gent, 13 November till 7 December 2015
boek